Renewable hydrogen production to deal with wind power surpluses and mitigate carbon dioxide emissions from oil refineries. (1st April 2022) - Nascimento da Silva, Gabriela; Rochedo, Pedro R.R.; Szklo, Alexandre
Highlights: Integration of wind energy, electrolysis, oxy-combustion and hydrogen storage. Potential to reduce up to 22% of the greenhouse gas emissions of a real oil refinery. A quarter of the wind surplus was used to produce hydrogen for the oil refinery. Electrolysis is only competitive with capital cost reductions and surplus electricity. Abstract: The variability and unpredictability of renewable energy sources represents a challenge to integrate these sources into power systems at high penetration levels. This study evaluates the use of wind energy surplus to produce hydrogen for hydrotreating units in oil refineries, replacing the steam methane reform, and to provide oxygen for oxy-combustion carbon dioxide (CO2 ) capture in Fluid Catalytic Cracking units. A case study in Rio Grande do Sul State, Brazil, was applied with six scenarios: two reference scenarios of hydrogen production, steam reform with and without carbon capture; and the other four regarding the use of wind energy to produce hydrogen and oxygen via water electrolysis. Results showed that the technological proposal has the potential to mitigate up to 22.11% of the greenhouse gas emissions in the refinery, from both hydrogen production and Fluid Catalytic Cracking units, at abatement costs in the range of −41 to 868 US/tCO2 . The lowest value depends on a severe reduction in electrolysis costs and the expected high penetration of renewable energies on electrical systems. Moreover, 26% of the total electricity surplus could be oriented to produce renewable hydrogen to supply the refinery demand, considering an electric system with 30% share of wind energy.